Problems of Interaction Between the Diplomatic Missions of the Ukrainian SSR and the RSFSR in Warsaw in the Process of Creating the USSR - Sergey A. Sklyarov (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Mezhdunarodnye otnosheni͡a, 2024)
The article examines the most acute problems and their solutions in the relations between the diplomats of the RSFSR and the Ukrainian SSR in Poland during the establishment of the Soviet Union (1921-1923). The relevance of the study is due to the introduction of recently declassified archival documents into the scientific discourse, as well as the growing interest in the topic in connection with the centennial of the creation of the USSR. The purpose of the study is to reveal the previously silenced facts and problems that accompanied the work of the foreign policy departments of the Soviet republics up to the rigid centralization and regulation of their activities, which occurred in the second half of 1923. So far, the issues of interaction between the diplomatic departments of the Soviet republics have remained virtually unexplored in the Russian historiography. At the same time, researchers in other post-Soviet countries are undoubtedly interested in the subject, which is limited by the materials of mainly local archives. The work is based on the methods of comparative historical analysis. The source base is based on the previously classified documents of the Archive of Foreign Policy of the Russian Federation, in particular, the correspondence of the RSFSR plenipotentiary representation with the central office of the People’s Commissariat for Foreign Affairs of the RSFSR in Moscow. As a result of the study, the author came to the conclusion that in 1921-1923 there were constant misunderstandings and conflict situations in the relations between the diplomatic missions of the RSFSR and the Ukrainian SSR operating in Warsaw. The higher officials in Moscow and Kharkov had to be constantly involved in their resolution. At the same time, it was not always possible to resolve disagreements and conflicts that arose promptly due to the lack of ready solutions in the specialized departments of the two republics. Many disagreements in the actions of Russian and Ukrainian diplomats reflected the numerous intra-party disputes over various issues of subordination and state structure that developed among the Bolsheviks who had won in Russia and Ukraine. The contradictions that arose, especially in the first stage of the establishment of diplomatic missions, were tried to be deepened and used for their own purposes by the Polish Ministry of Foreign Affairs.